Review of fuel failures in water cooled reactors. - Inozemtsev, Victor (IAEA nuclear energy series ;, 2010)
This publication responds to the growing awareness of a need for open discussion and concerted actions to improve nuclear fuel reliability. It contains unique worldwide statistics on fuel failure rates, covering about 96% of water cooled reactor fuels. This gives the most representative picture of fuel reliability available in the open literature and presents a number of valuable conclusions. The publication also describes modern methods of detection and examination of fuel failures, analyzes their mechanisms and root causes, and recommends failure prevention and mitigation measures. These data and information are important elements for closing the circle of the fuel quality management system through providing feedback information about fuel performance--Publisher's description.